The Influence of Media Violence Exposure on Children: An Analytical Study of Parents Perspectives - Dr. Zamir Ahmed; Dr. Sajid Manzoor (JECCE, 2025)
This paper examines the impact of rough media content on children as per point of view of their guardians. It was explored how exposure to savagery in TV and video recreations impacts children's behavior. Survey, research method was employed. Data was collected from 150 mothers of children in Islamabad through stratified random sampling technique, divided equally between housewives and working women to ensure diverse perspectives. The Cultivation Theory was applied in this study. According to the results, children who frequently watch violent content on TV programs and play violent video games exhibit increased aggression and behavioral changes. Parents reported that their children watched violent action content on TV or in video games, leading to more aggressive interactions with their friends and family members. The results showed that many children spend a lot of time watching TV and playing video games, especially fighting games, which might affect how they behave. Parents observed the changes in their behavior, which led to aggression and violence, and this happened due to the introduction of savage media substance. Overall, this research shows important results about how media violence affects children's behavior and highlights the important role that parents play in watching and guiding their children's media use.